The effective republic : administration and constitution in the thought of Alexander Hamilton - Flaumenhaft, Harvey, 1938- (E-Duke books scholarly collection., 1992)
The United States has been distinguished among free governments as a "presidential" republic. In The Effective Republic, Harvey Flaumenhaft shows how the study of Alexander Hamilton's political thought opens the way to understanding the nature of this republic and the reasons for its development. Although Hamilton exterted an extraordinary influence on American institutions, his contribution and the thinking behind it often have been obscured and misconstrued by piecemeal approaches to his voluminous writings. Here, Flaumenhaft draws upon more than two dozen volumes of Hamilton'